Correction to: Probabilistic maps on bistable vibration energy harvesters (Nonlinear Dynamics, (2023), 111, 22, (20821-20840), 10.1007/s11071-023-08864-2) - Norenberg, João Pedro [UNESP]; Cunha Jr, Americo; da Silva, Samuel [UNESP]; Varoto, Paulo Sergio (Springer Nature, 2023)
In the aforementioned article, the text of the Code Availability section was inadvertently placed within the Conflict of interest section. Please find the correct format below: Code availability: The simulations presented in this paper were performed using the computational code STONEHENGE—Suite for Nonlinear Analysis of Energy Harvesting Systems [33], which is available for free on GitHub [30]. Conflict of interest: The authors declare they have no conflict of interest. Springer wishes to apologize for any inconvenience caused.